Peran Kemandirian Belajar dalam Memediasi Pengaruh Motivasi Berprestasi terhadap Prestasi Belajar Mahasiswa Selama Pembelajaran Daring - Matsani, Nurul; Rafsanjani, M. Arief (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze and examine the role of independent learning in mediating the effect of achievement motivation on student achievement during online learning. Respondents of this study were 158 active students of the Department of Economic Education, UNESA, batch 2018. Data collection techniques were through questionnaires and documentation, then the data were analyzed using the SEM (Structural Equation Modeling) test. The results of this study indicate that achievement motivation has a direct and significant effect on learning achievement. Achievement motivation has a direct and significant effect on learning independence. Learning independence has no direct and insignificant effect on learning achievement. and achievement motivation has an indirect effect on learning achievement through independent learning with a total value of 20%.